HDL particles incorporate into lipid bilayers – a combined AFM and single molecule fluorescence microscopy study. Issue 1 (December 2017) - Plochberger, Birgit; Röhrl, Clemens; Preiner, Johannes; Rankl, Christian; Brameshuber, Mario; Madl, Josef; Bittman, Robert; Ros, Robert; Sezgin, Erdinc; Eggeling, Christian; Hinterdorfer, Peter; Stangl, Herbert; et al.
Abstract The process, how lipids are removed from the circulation and transferred from high density lipoprotein (HDL) – a main carrier of cholesterol in the blood stream – to cells, is highly complex. HDL particles are captured from the blood stream by the scavenger receptor, class B, type I (SR-BI), the so-called HDL receptor. The details in subsequent lipid-transfer process, however, have not yet been completely understood. The transfer has been proposed to occur directly at the cell surface across an unstirred water layer, via a hydrophobic channel in the receptor, or after HDL endocytosis. The role of the target lipid membrane for the transfer process, however, has largely been overlooked. Here, we studied at the single molecule level how HDL particles interact with synthetic lipid membranes. Using (high-speed) atomic force microscopy and fluorescence correlation spectroscopy (FCS) we found out that, upon contact with the membrane, HDL becomes integrated into the lipid bilayer. Combined force and single molecule fluorescence microscopy allowed us to directly monitor the transfer process of fluorescently labelled amphiphilic lipid probe from HDL particles to the lipid bilayer upon contact.